Construction of a self-sufficient DNA circuit for amplified detection of kanamycin. (30th August 2023) - Li, Yumeng; Si, Qingyang; Liu, Chuanyi; Huang, Ziling; Chen, Qingmin; Jiao, Tianhui; Chen, Xiaomei; Chen, Quansheng; Wei, Jie
Graphical abstract: Highlights: A robust DNA amplification strategy was designed for kanamycin detection in liquid food matrices. Self-driven hybridization chain reaction (SHCR) effectively enhanced FRET signal. The sensitivity of SHCR system is 5, 800-fold higher than that of HCR system. Reliable detection of kanamycin in milk and honey was achieved. Abstract: Improper use of kanamycin can lead to trace kanamycin residues in animal-derived foods, which can pose a potential threat to public health. Isothermal enzyme-free DNA circuits have provided a versatile toolbox for detecting kanamycin residues in complicated food samples, yet they are always limited by low amplification efficiency and intricate design. Herein, we present a simple-yet-robust nonenzymatic self-driven hybridization chain reaction (SHCR) amplifier for kanamycin determination with 5800-fold sensitivity over that of the conventional HCR circuit. The analyte kanamycin-activated SHCR circuitry can generate numerous new initiators to promote the reaction and improve the amplification efficiency, thus achieving an exponential signal gain. With precise target recognition and multilayer amplification capability, our self-sustainable SHCR aptasensor facilitated the highly sensitive and reliable analysis of kanamycin in buffer, milk, and honey samples, thus holding great potential for the amplified detection of trace contaminants in liquid food matrices.